Investigation of fruit peel extracts as sources for compounds with antioxidant and antiproliferative activities against human cell lines - Khonkarn R. (2014)
The aim of this study was to evaluate antioxidant activity and cytotoxicity against human cell lines of fruit peel extracts from rambutan, mangosteen and coconut. The highest antioxidant activity was found from rambutan peel crude extract where the highest radical scavenging capacity via ABTS assay was from its ethyl acetate fraction with a TEAC value of 23.0mM/mg and the highest ferric ion reduction activity via FRAP assay was from its methanol fraction with an EC value of 20.2mM/mg. Importantly, using both assays, these fractions had a higher antioxidant activity than butylated hydroxyl toluene and vitamin E. It was shown that the ethyl acetate fraction of rambutan peel had the highest polyphenolic content with a gallic acid equivalent of 2.3mg/mL. The results indicate that the polyphenolic compounds are responsible for the observed antioxidant activity of the extracts. Interestingly, the hexane fraction of coconut peel showed a potent cytotoxic effect on KB cell line by MTT assay (IC50=7.7μg/mL), and no detectable cytotoxicity toward normal cells. We concluded that the ethyl acetate fraction of rambutan peel is a promising resource for potential novel antioxidant agents whereas the hexane fraction of coconut peel may contain novel anticancer compounds. © 2010 Elsevier Ltd.